Online stress monitoring during laser-directed energy deposition based on dynamic contour method - Yi Lu; Wenbo Li; Jian Dong; Chen Wang; Rongqi Shen; Kelin Zhu; Bin Wu; Guifang Sun; Jing Rao (Virtual and Physical Prototyping)
Deformation and cracking caused by internal stress have been a long-standing challenge in the field of metal additive manufacturing. This paper presents a novel method for real-time stress assessment of laser-directed energy deposition (LDED) based on the shrinkage phenomenon of deposition layer – the Dynamic Contour Method (DCM). It integrates machine vision, three-dimensional reconstruction based on actual morphology, and numerical simulation to calculate rapidly stress development during the LDED process. Meanwhile, a mapping relationship between the surface shrinkage of the deposition layer and stress is established, providing a theoretical basis for the DCM. Regarding the validation of this method, the DCM simulations are compared with the experimentally calibrated thermo-mechanical coupling simulations. The results show a high degree of consistency, demonstrating the feasibility and accuracy of the DCM. This method provides a new digital twin framework for additive manufacturing.